High-resolution InSAR regional soil water storage mapping above permafrost - Y. Wu; J. Chen; J. Chen; J. Chen; M. B. Cardenas; G. W. Kling (Hydrology and Earth System Sciences, 2025)
The hydrology of thawing permafrost affects the fate of the vast amount of permafrost carbon, due to its controls on waterlogging, redox status, and transport. However, regional mapping of soil water storage in the soil layer that experiences the annual freeze–thaw cycle above permafrost, known as the active layer, remains a formidable challenge over remote Arctic regions. This study shows that interferometric synthetic aperture radar (InSAR) observations can be used to estimate the amount of soil water originating from the active-layer seasonal thaw. Our ALOS InSAR results, validated by in situ observations, show that the equivalent thickness of the soil water that experiences the annual freeze–thaw cycle ranges from 0 to 75 cm in a 60 km×100 km area near the Toolik Field Station on the North Slope of Alaska. Notably, the spatial distribution of the soil water correlates with surface topography and land vegetation cover types. We found that pixel-mismatching of the topographic map and radar images is the primary error source in the Toolik ALOS InSAR data. The amount of pixel misregistration, the local slope, and the InSAR perpendicular baseline influence the observed errors in InSAR line-of-sight (LOS) distance measurements. For most of the study area with a percent slope of less than 5 %, the LOS error from pixel misregistration is less than 1 cm, translating to less than 14 cm of error in the soil water estimates.